Utilization of Professional Allowances in Developing Teacher Professionalism at State Elementary School 9 Sembawa - M. Awaludin; Edi Harapan; Andi Rahman (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aimed to explore how teachers utilize the Teacher Professional Allowance (TPG) to enhance their professional competencies at SD Negeri 9 Sembawa. A qualitative descriptive approach was employed involving the principal and certified teachers receiving the Teacher Professional Allowance as research informants selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation and analyzed using the Miles, Huberman, and Saldaña interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the Teacher Professional Allowance contributes significantly to strengthening teachers' pedagogical, professional, social, and personal competencies through participation in professional development activities, acquisition of learning resources, improvement of digital literacy, and instructional innovation. Nevertheless, the effectiveness of TPG utilization is influenced by leadership support, organizational culture, access to professional training, and teachers' individual motivation. This study contributes to educational management by demonstrating that professional allowances function not merely as financial incentives but also as strategic instruments for sustainable teacher professional development when supported by effective school management.